2022
DOI: 10.1007/s10570-022-04459-z
|View full text |Cite
|
Sign up to set email alerts
|

Palladium supported on ethylenediaminetetraacetic acid functionalized cellulose: synthesis, characterization, and its application in carbon–carbon cross-coupling reactions

Abstract: Through the esteri cation of cellulose (Cell) with ethylenediaminetetraacetic dianhydride, ethylenediaminetetraacetic acid-functionalized cellulose (Cell-EDTA) was conveniently obtained. Furtherly a novel and e cient Cell-EDTA-supported palladium catalyst (Pd@Cell-EDTA) was easily prepared via coordination of Cell-EDTA with PdCl 2 . The as-prepared Pd@Cell-EDTA was fully characterized by inductively coupled plasma atomic emission spectrometry (ICP-AES), X-ray photoelectron spectroscopy (XPS), Flourier transfor… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(6 citation statements)
references
References 42 publications
0
6
0
Order By: Relevance
“…SEM images of the catalyst after the second run revealed the agglomeration of Pd nanoparticles on the surface of the catalyst, which is the major reason for the drop in the product yields as shown in Figure 8. The yield after the second run reaction was still high (>90%) and dropped to 80% after the fifth run but dramatically decreased to 50% after the sixth 1 a CS-NNSB-Pd(II) (0.006) -50 c 0.08 97 Baran [28] 2 ImmPd-MNPs (0.14) TBAB/H 2 O r.t. 0.3 93 Hajipour and Tavangar-Rizi [29] 3 CS-Biguanidine/Pd (0.15) EtOH/H 2 O 40 1 98 Veisi et al [32] 4 Pd@Cell-EDTA (0.05) EtOH/H 2 O 78 0.5 96 Xu et al [11] 5 PdNPs@chitosan (0.1) TBAB 90 5 97 Cotugno et al [17] 6 PdNPs/GO-TETA (0.01) DMF/H 2 O 90 0.4 98 Mirza-Aghayan et al [19] 7 F e 3 O 4 @SiO 2 /PropylSB@Pd (0.1) H 2 O/EtOH 80 c 0.5 92 Hasan et al [6] 8 F e 3 O 4 /CS-Me@Pd (0.003) EtOH/H 2 O 50 30 98 Wang et al [36] 9 Cell-Sc-Pd(II) (0.002) EtOH/H 2 O 70 1.5 74 Pharande et al [12] 10 Fe 3 O 4 -CS@tet-Pd(II) EtOH/H 2 O 90 2.2 91 Nasrollahzadeh et al [40] 11 a Fe 3 O 4 @Guanidine-Pd (0.22) H 2 O 70 0.5 90 Halligudra et al [8] 12 Fe 3 O 4 @SiO 2 -TCT-GA-Pd(0) (0.12) EtOH/H 2 O 50 1.5 95 Eslahi et al [9] 13 PdNPs@CS/δ-FeOOH (0.05) EtOH/H 2 O r.t. 3 91 Çalıs ¸kan and Baran [21] 14 Fe 3 O 4 @MCM41@NHC@Pd (0.01) run. From these results, it can be concluded that the catalyst was effective for five runs.…”
Section: Recycle Of the Catalystmentioning
confidence: 99%
See 2 more Smart Citations
“…SEM images of the catalyst after the second run revealed the agglomeration of Pd nanoparticles on the surface of the catalyst, which is the major reason for the drop in the product yields as shown in Figure 8. The yield after the second run reaction was still high (>90%) and dropped to 80% after the fifth run but dramatically decreased to 50% after the sixth 1 a CS-NNSB-Pd(II) (0.006) -50 c 0.08 97 Baran [28] 2 ImmPd-MNPs (0.14) TBAB/H 2 O r.t. 0.3 93 Hajipour and Tavangar-Rizi [29] 3 CS-Biguanidine/Pd (0.15) EtOH/H 2 O 40 1 98 Veisi et al [32] 4 Pd@Cell-EDTA (0.05) EtOH/H 2 O 78 0.5 96 Xu et al [11] 5 PdNPs@chitosan (0.1) TBAB 90 5 97 Cotugno et al [17] 6 PdNPs/GO-TETA (0.01) DMF/H 2 O 90 0.4 98 Mirza-Aghayan et al [19] 7 F e 3 O 4 @SiO 2 /PropylSB@Pd (0.1) H 2 O/EtOH 80 c 0.5 92 Hasan et al [6] 8 F e 3 O 4 /CS-Me@Pd (0.003) EtOH/H 2 O 50 30 98 Wang et al [36] 9 Cell-Sc-Pd(II) (0.002) EtOH/H 2 O 70 1.5 74 Pharande et al [12] 10 Fe 3 O 4 -CS@tet-Pd(II) EtOH/H 2 O 90 2.2 91 Nasrollahzadeh et al [40] 11 a Fe 3 O 4 @Guanidine-Pd (0.22) H 2 O 70 0.5 90 Halligudra et al [8] 12 Fe 3 O 4 @SiO 2 -TCT-GA-Pd(0) (0.12) EtOH/H 2 O 50 1.5 95 Eslahi et al [9] 13 PdNPs@CS/δ-FeOOH (0.05) EtOH/H 2 O r.t. 3 91 Çalıs ¸kan and Baran [21] 14 Fe 3 O 4 @MCM41@NHC@Pd (0.01) run. From these results, it can be concluded that the catalyst was effective for five runs.…”
Section: Recycle Of the Catalystmentioning
confidence: 99%
“…[1][2][3] Among the crosscoupling reactions, the Suzuki-Miyaura reaction is one of the powerful tools to create a carbon-carbon bond from the cross-coupling of aryl boronic acid and aryl halides using a palladium catalyst to synthesize biaryls for industrial uses related to pharmaceuticals, agrochemicals, polymers, and materials. [4,5] Recently, many research groups have demonstrated the use of various kinds of materials as catalyst support for the Suzuki-Miyaura reaction, including organic and inorganic compounds such as metal oxides, [6][7][8][9][10] polymers, [11][12][13][14][15][16][17][18] carbon materials, [19,20] and composite materials. [21,22] Among these support materials, natural polymers have attracted much attention due to their availability, nontoxicity, biodegradability, and low cost.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The palladium-catalyzed Suzuki cross-coupling reaction, which is the widely used protocol for the preparation of biphenyls, [1][2][3][4][5] has become one of the key organic unit reactions for construction of carbon-carbon bonds, resulting in an extensive range of fine chemical industry, pharmaceutical synthesis and organic functional materials. [6][7][8][9] However, Suzuki coupling reactions are usually carried out in organic solvents and involve the use of phosphine ligands, [10] which limits the further application.…”
Section: Introductionmentioning
confidence: 99%
“…Porous organic polymers, POPs, have showed high efficiency as heterogeneous catalysts due to properties such as high microporosity with tunable pore volume, high specific surface area, the possibility to incorporate high catalyst loadings or excellent thermal and chemical stability. In recent years, the inclusion of catalysts confined in very small pores has resulted in materials with excellent reaction yields, high turnover number (TON) and turnover frequency (TOF), high regioselectivities, high recyclability and low metallic contamination in the products obtained [1][2][3][4][5][6][7][8]. These POPs can be synthesized by multiple methodologies [9].…”
Section: Introductionmentioning
confidence: 99%